Towards wellbeing: monitoring poverty in Kutai Barat, Indonesia - Gonner, C.; Cahyat, A.; Haug, M.; Limberg, G. (Center for International Forestry Research, 2007)
Poverty is a persistent problem throughout Indonesia. Seven years after decentralisation began there is little improvement in the wellbeing of rural people. Local governments have received new opportunities and responsibilities for development, but few districts have the necessary capacity and experience to effectively reduce poverty. This report provides a portrait of household poverty and wellbeing in Kutai Barat, a district that was only established in 1999. The results of a survey of more than 10,000 households from 222 villages, 6 in-depth community studies, remote sensing and several workshops, show which aspects of wellbeing are in critical condition and where interventions are most urgently needed. The report analyses poverty causes and gives practical recommendations to help the local government improve its development planning and poverty reduction.